"التدوين المرئي في الجزائر ودوره في تعليم اللغة الإنجليزية" دراسة تحليلية لعينة من الفيديوهات التعليمية بقناة اليوتيوب Mister Amine - عاشور, هناء (جامعة الوادي - University of Eloued, 2021)
من خلال هذه الورقة البحثية نتناول موضوع في غاية الأهمية والمتمثل في الدور الذي يلعبه التدوين المرئي في الجزائر في تعليم اللغة الإنجليزية، وذلك من خلال إجراء دراسة تحليلية بالإعتماد على إستمارة تحليل مضمون لعينة من الفيديوهات التعليمية لقناة اليوتيوب Mister Amine التي حاول من خلالها تعليم المتابعين اللغة الإنجليزية بطريقة مبسطة وبسيطة حيث إعتمد في شرحه على إستخدام اللهجة الجزائرية ليكون مضمون دروسه مفهوما للمبتدئين. أفرزت نتائج هذه الدراسة التحليلية أن صاحب القناة الأستاذ محمد أمين مزج بين الأساليب والقوالب الفنية وكذا أماكن التصوير وحاول التركيز في دروسه على تعليم التعبير الصحيح وتزويد المتابعين بمصطلحات جديدة في كل فيديو، لإثراء رصيدهم اللغوي وغيرها من الأساليب التي حاول توظيفها في فيديوهاته لتحقيق الهدف المرجو من إنشاء قناته والمتمثل في تعليم اللغة الإنجليزية للجزائريين. Through this research paper, we address a very important topic which is the role that visual blogging plays in Algeria to teach English language by conducting an analytical study based on a content analysis form of a sample of the educational videos of Mister Amine's YouTube channel which he tried to teach the followers English language in a simple way, he relied in his explanation on the use of the Algerian dialect to make the content of his lessons understandable for beginners The results of this analytical study revealed that the owner of the channel, Professor Mohamed Amine mixed styles and artistic forms as well as photographed places and tried to focus in his lessons on teaching the correct expressions and providing followers with new terms in every video to enrich their linguistic balance and other methods that he tried to employ in order to achieve the desired goal of his channel which is teaching English to Algerians.
Visual blogging in Algeria and its role in teaching English Analytical study of a sample of educational videos from Mister Amine's YouTube channel
مقال
Keywords: التدوين ، التدوين المرئي ، اليوتيوب ، الفيديوهات التعليمية ، تعليم اللغات ، اللغة الإنجليزية; Blogging, vlogging, YouTube, Educational videos, Teaching Languages, English Language.